Stock market investment and the influential factors in investment decision making: a study on Kelantanese investors / Zainudin Awang, Nik Maheran Nik Muhammad and Mohamad Safri Ya - Awang, Zainudin; Nik Muhammad, Nik Maheran; Ya, Mohamad Safri (2003)
Stock exchange offers an investment opportunity for the public to participate in the economy. For the corporate sectors, stock market is the place where they can raise the fund to further enhance their business. The investors can buy the shares of the company they want to invest, and they can also sell back their holdings when they obtain enough profit or when they want to shift their portfolio. The questions of when to enter the market, why are they buying the particular shares now, what is their expectation on the company's financial performance and hence their capital appreciation, who are the key personnel in the company's board of directors, which factors a re being considered in reaching an investment decision, where is the company's position among their competitors, and how likely is that investment provide the expected return are among the questions that the investors must be able to answer before making an investment commitment. Some investors make their decision after studying certain fundamental aspects of the company, but, unfortunately there are also investors who are influenced by the speculative factors. In other words, different investors might use different methods and consider different factors before reaching their investment decision. In short, all investors are aiming for profits - in the form of dividend payment, bonus issues, or capital appreciation. This paper was trying to identify what criteria the K elantanese investors normally use in reaching their investment decision. The researchers a re interested to identify whether the criteria used by Kelantanese investors are purely speculative in nature or there are some fundamental aspects being considered. The study wanted to identify the level of awareness of the Kelantanese investors toward the external factors such as the foreign market performance, foreign economic scenario, and world events that might contribute the significant impacts on the performance of the Kuala Lumpur Stock Exchange (KLSE). The study found the demographic variables such as age levels, levels of education and types of occupation of investors have significant correlation with various decision-making criteria. Among decision making criteria being studied are company's takeover and merger, dividend payment, right and bonus issues, market tips, advice from remisier, active stocks of the day, company's performance, company's management expertise, and corporate governance of the company.